Functional and morphological analysis of isolates of phylloplane and rhizoplane endophytic bacteria interacting in different cocoa production systems in the Amazon - Alves-Júnior, Miguel; de Sousa, Fabiana Oliveira; Silva, Thays Ferreira; Albino, Ulisses Brigatto; Garcia, Magali Gonçalves; Moreira, Simone Maria Costa de Oliveira; Vieira, Marcos Ribeiro da Silva (Current research in microbial sciences, 2021)
•The largest number of endophytic bacteria was isolated from the root of cocoa trees (Theobroma cacao L.).•The most expressive functional characterization was amylolytic activity.•The similarity analysis formed two clusters with the isolates CS R 2.4 and CS R 2.25 with 100% similarity.•Isolates of endophytic bacteria show ability to antagonist activity.•Frist study in different cocoa production systems in the state of Pará, Brazil. Endophytic bacteria colonize different internal tissues of plants without damaging their cells. They can establish themselves in the same niche as other microorganisms and develop antagonistic activities against phytopathogens. There is little research on the functional and morphological characterization of these bacteria in production systems in the Amazon. Thus, the objective of this work was to functionally and morphologically characterize endophytic bacteria isolated from cocoa trees (Theobroma cacao L.) and evaluate their antagonistic potential against phytopathogens. A total of 197 endophytic bacteria isolates were obtained from leaves and roots of cocoa plants with different production systems and at different times of the year. The characterization of functional groups consisted of proteolytic, amylolytic and cellulolytic activity and ability to fix nitrogen and solubilize phosphate. Morphological diversity was evaluated mainly according to the following parameters: shape, color, size and elevation of the colony. Thirteen isolates of endophytic bacteria, selected by cluster analysis, were used to evaluate the antagonistic potential in paired trials against four species of phytopathogenic fungi. The largest amount of endophytic bacteria was isolated from the root (95.9%), in the dry season. The most expressive activities with regards to the enzyme index were amylolytic (71.9%), proteolytic (70.2%) and nitrogen fixing (38.6%), respectively. The similarity analysis formed two clusters with isolates CS R 2.4 and CS R 2.25 exhibiting 100% similarity. Five isolates displayed inhibitory activity against phytopathogenic fungi, most notably isolate TS R 2.19, which exhibited antagonistic activity against all fungi and mycelial growth inhibition rates between 25.7% and 50.7%. Understanding the interaction between endophytes in cocoa plants is important as a possible additional tool in biological control. Our studies are incipient and the first to be carried out in different cocoa production systems in the state of Pará, Brazil.